New daily persistent headache with isolated sphenoiditis in children - Jeongho Lee; Minhee Rhee; Eun Sook Suh (Korean Pediatric Society, 2015)
Isolated sphenoid sinusitis is a rare disease in children, and its symptoms are often nonspecific and confusing. Rarely, severe headache can be the first or only symptom of isolated sphenoid sinusitis. New daily persistent headache (NDPH) is a form of chronic daily headache that may have features of both migraines and tension-type headaches. NDPH is difficult to diagnose and requires a multifaceted approach. Here, we report on a 10-year-old boy and an 11-year-old girl who both presented with typical NDPH symptoms. These patients had no nasal symptoms or signs of infection. Neither nonsteroidal anti-inflammatory drugs nor topiramate had any effect on the headaches. Their neurological and ophthalmological examinations were normal. The results of routine blood work, including thyroid function tests, inflammatory markers, complete blood count, tests for viral infection, and a metabolic panel, were normal. A brain magnetic resonance imaging scan showed isolated sphenoid sinusitis. Both patients' symptoms resolved completely after approximately 1 month of oral antibiotics for sinusitis.